TRAINING NEEDS ASSESSMENT OF AGRI-INPUT DEALERS - KADIRI MOHAN*, P.GANESH KUMAR; P.RAJASEKHAR (The Journal of Research ANGRAU, 2019)
The sample of 120 Agri input dealers was studied for assessment of their training needs in Chittoor district of Andhra Pradesh during 2018-19. The results revealed that the major crops for which trainings requiredarerice, groundnut and mango. Germination tests for testing viability of seeds and seed materials,labeling and seed certification were among the top needed training areasunder the aspect of seeds and planting material. Types ofmanures and fertilizers available and dosage calculations of straight and complex fertilizers were the most needed training areas under manures and fertilizers aspect. Most important training needs related to agrochemicals aspect are pest and diseases identification in major crops,pesticides and their mode of action.Regarding farm machinery, latest farm implements and their maintenancewas identified as an important training need. Further, in addition to agricultural aspects, input dealers expressed the necessity of training requirement on business licensing, renewals,taxation and billing. Respondents preferred to have trainings of one-week duration, during the period of February to April with a periodicity once in every year for organising the trainings.